2014
DOI: 10.4067/s0718-58392014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the phenolic extract from jabuticabeira (Myrciaria cauliflora (Mart.) O. Berg) fruit skins on Spodoptera frugiperda

Abstract: Fall armyworm, Spodoptera frugiperda J.E. Smith, 1797 (Lepidoptera: Noctuidae) is the main pest of maize, besides attacking sorghum and cotton crops. The control of this pest has been accomplished mainly with the use of synthetic insecticides but, due to the growing concern about the environment and food quality, phenolic compounds have shown their potential for the biological control of this insect. Thus, the objective of the present study was to evaluate the efficiency of the extract of jabuticabeira, Myrcia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
(16 reference statements)
1
21
0
Order By: Relevance
“…Given that there are no available research data on the use of ABF in pest control, the results obtained in this study complement those of Santos et al (2013) and Alves et al (2014), who used natural products such as cassava Manihot esculenta Crantz leaf powder and jabuticaba skin flour, respectively, to control S. frugiperda caterpillars.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Given that there are no available research data on the use of ABF in pest control, the results obtained in this study complement those of Santos et al (2013) and Alves et al (2014), who used natural products such as cassava Manihot esculenta Crantz leaf powder and jabuticaba skin flour, respectively, to control S. frugiperda caterpillars.…”
Section: Resultssupporting
confidence: 66%
“…In contrast, Melo et al (2011) studied grape and guava bagasse and found gallic acid, epicatechin, quercetin, isovanillic acid, p-coumaric acid, caffeic acid, and resveratrol. Alves et al (2014) reported gallic acid, gallocatechin, catechin, epicatechin, ellagic acid, and salicylic acid in jabuticaba (Myrciaria cauliflora (Mart.) O. Berg) skin flour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to those factors, organic cultivation has been increased, replacing the use of chemical insecticides by alternative methods of pest control (Uchino et al, 2015). A promising alternative to control fall armyworm is the use of plants secondary metabolites (Tavares et al, 2009;Alves et al, 2014). These chemicals compounds produced by plants can induce deleterious effects on insects such as weight loss, fecundity and fertility reduction, increasing duration of immature stages, feeding deterrence, ultra structural modification on tissues, changes in some nutritional parameters, and inhibition of digestive enzymes, which is lethal to some insects (Malau and James, 2008;Nathan et al, 2008;Correia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%